Hubungan Self Care dan Kualitas Hidup Pasien Gagal Jantung - Simanjuntak, Andreas (E-Jurnal Medika Udayana, 2021)
Heart failure is a heart condition that is difficult to pump blood throughout the body, has been ensure is caused by damage to heart function and result in disruption of activities that reduce the desire of patients to do self care and will affect the quality of life of patients. The aim of this study was to determine the relationship between self care with the quality of life of heart failure patients. This analytic study uses a cross sectional study design. The sample of this study were 160 patients selected by consecutive sampling method and analyzed by Chi-square test. The results showed there was a relationship between self care, age, education level, and family income with the quality of life of heart failure patients (p <0.05), while sex does not have a relationship with the quality of life of heart failure patients.